“They Make No Contribution!” versus “We Should Make Friends with Them!”—American Domestic Students’ Perception of Chinese International Students’ Reticence and Face - Zhu, Yi; Bresnahan, Mary (Journal of International Students, 2018)
This project examined both quantitative and qualitative data about how American domestic undergraduates perceived Chinese international students’ (CISs) reticence and face concerns. A quasi-experimental design about American students’ ratings of a fictional CIS described in scenarios demonstrated that the reticent CIS was rated as more typical, less likable, and less socially-approved. A thematic analysis of American students’ impression about CISs suggested: 1) some Americans stigmatized CISs due to their poor English and reticence in classroom; 2) others were more open-minded to approach CISs’ reticence with intercultural communication competence by taking CISs’ perspective. The findings indicated: the stereotype that typical CISs are reticent leads to Americans’ negative evaluations of CISs; while perspective-taking skills resulted in better intercultural-communication experience.